PENGARUH KUALITAS PRODUK, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN MARTABAK ALONG 89 LAMPUNG - Wijaya, Ricky; Habiburahman, Habiburahman (Politeknik Negeri Ambon, 2023)
This research intends to analyse the effect of the product quality, price, and location on purchasing decisions in an MSME. Researchers took samples namely Martabak Along 89 Lampung and using consumers from Martabak Along 89 Lampung as respondents for this research also researchers distributed questionnaires via google form. The sampling technique used was accidental sampling and there were 55 respondents in this research. The analytical method used is multiple linear regression analysis. The result of this research concludes that product quality, price, and location have a significant positive influence on purchasing decisions at Martabak Along 89 Lampung.